Perception and practice of household solid waste management practices in rural Mysuru district: a cross-sectional study - M., Rakesh; Ravali, Annaram; Shruddha; D., Sunil Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Effective household solid waste management (SWM) is vital for public health, environmental quality, and sustainable living. With rising global waste production, understanding current practices is essential for policy and system improvements. Objectives were to assess the practice and perception of household SWM among rural population Methods: A community-based cross-sectional study was conducted in Suttur, Mysuru. Using systematic random sampling 200 households were selected. Data was collected using a validated, semi-structured questionnaire, including socio-demographic profiles, knowledge, and waste management practices. Analysis was performed using SPSS version 26 and chi-square tests were used to identify significant associations (p<0.05). Results: Participants aged 18-30 years constituted 48% of the sample, with a nearly balanced gender distribution (49.5% male, 50.5% female). Waste segregation was practiced by 70% of households. Daily waste disposal was reported by 58.5% of participants, primarily using corporation dustbins (72%). Significant associations were found between awareness scores and age (p<0.0001), education level (p<0.001), type of house (p<0.001), socio-economic status (p=0.007), and marital status (p=0.0001). Graduates demonstrated the highest levels of excellent knowledge (43.2%), while illiterates had a significant proportion of poor knowledge (50%). Conclusions: The study highlights the need for improved waste management systems, enhanced public awareness, and stricter regulations to address current environmental and health risks. Future research should focus on evaluating intervention effectiveness and exploring innovative waste management solutions in rural areas